Sifat Antioksidasi Bubuk Kunyit dan Pengaruhnya terhadap SGPT-SGOT Tikus Percobaan - Indarto, Tri; Pujimulyani, Dwiyati; Tamaroh, Siti (Jurnal Teknologi dan Industri Pangan, 2024)
The communities believed that consumption of turmeric rhizomes can maintain hepatic health. The purpose of the research was to determine the antioxidation properties of turmeric powder (BK) and its effect on serum glutamate pyruvate transaminase (SGPT) and serum glutamate oxaloacetate transaminase (SGOT) levels in vivo in rats injected with Staphylococcus aureus 1´108 cell/mL. The study involved 24 rats categorized into 4 groups. All rats were acclimatized for 1 week and then given treatment according to their respective standard diets. The treatment was administered for 16 days and injected with S. aureus 1´108 cell/mL. The study was conducted using CRD factorial pattern 2 treatments, including variations of turmeric rhizomes (main and branches), and the length of steam blanching time (0, 2.5, 5, 7.5, and 10 min). The analyses included antioxidant activity, total phenolics, flavonoids, tannins, and curcumin as well as superoxide dismutase (SOD), SGPT, and SGOT in vivo. As a result, turmeric powder from main rhizome with a steam blanching time of 5 min was selected and it showed the greatest antioxidant activity by ferric reducing antioxidant power (FRAP) method, total phenolics, flavonoids, and tannins respectively, namely 96.89 Ferro E/g, 24.46 mg GAE/g, 12.05 mg QE/g and 0.35 mg CE/g. The results showed that rats given selected turmeric (main rhizome, 5 min steam blanching) that injected with S. aureus had SOD, SGPT, and SGOT values of 72.92%, 19.50 U/L, and 38.03 U/L respectively.